Toll-Like Receptor Ligand-Induced Liver Injury in D-Galactosamine-Sensitized Mice: Differences between TLR7/8 and TLR9 Ligands, Cytokine Patterns, and Cross-Tolerance Induction by TLR2 Ligand Pretreatment - Reiko Seki (Journal of Immunology Research)
Administration of Toll-like receptor ligands (TLRLs) is known to cause liver injury in D-galN-sensitized mice. In the present study, we aimed to complement preceding reports on the TLRL/D-galN system by analyzing comparisons among TLRLs, mouse strain dependence, effects on serum levels of cytokines, and effects of sequential administrations of different TLRLs. In a preliminary set of analyses, we first confirmed that liver failure can be induced by diverse TLRLs, including LTA and R848 in combination with D-galN. Analysis using TLR4-deficient mice excluded potential confounding effects of endogenous TLR4Ls that include those referred to as DAMPs in CpG DNA/D-galN hepatotoxicity. Subsequently, we showed that LTA pretreatment could prevent mortality in both CpG DNA/D-galN- and R848/D-galN-treated mice compared to without pretreatment. Incidentally, we observed that without the LTA pretreatment, CpG DNA/D-galN showed relatively higher liver-specific toxicity whereas R848/D-galN showed more symptoms of multiple organ failure. These findings suggest that, in D-galN-sensitized mice, different TLRLs not only show similarity in the ability to induce hepatic injury but also exhibit distinctive abilities in inducing systemic inflammation and multiple organ failure. These findings also suggest the potential usefulness of cross-tolerance induction using LTA in the prevention of organ failure in TLRL-mediated acute inflammation.